2012
DOI: 10.1097/aog.0b013e31823dc015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Progestin Compared With Combined Oral Contraceptive Pills on Lactation

Abstract: Objective To estimate the effect of progestin-only vs. combined hormonal contraceptive pills on rates of breastfeeding continuation in postpartum women. Secondary outcomes include infant growth parameters, contraceptive method continuation and patient satisfaction with breastfeeding and contraceptive method. Methods In this randomized controlled trial, postpartum breastfeeding women who desired oral contraceptives were assigned to progestin-only vs. combined hormonal contraceptive pills. At two and eight wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 13 publications
(13 reference statements)
1
34
0
1
Order By: Relevance
“…79 A recently published double-blind randomized trial compared the effect of initiating progesterone-only contraceptives (0.35 mg norethindrone) with COCs (0.035 mg ethinyl estradiol 1 1 mg norethindrone) at 2 weeks postpartum. 80 This study found that there was no difference in continuation of breastfeeding between the 2 groups at 8 weeks (64.1% combined pills vs 63.5% progestin only) or 6 months. 80 In both groups, women who supplemented their infants with formula or had concerns of inadequate milk supply were more likely to stop breastfeeding.…”
Section: Contraceptivesmentioning
confidence: 79%
See 2 more Smart Citations
“…79 A recently published double-blind randomized trial compared the effect of initiating progesterone-only contraceptives (0.35 mg norethindrone) with COCs (0.035 mg ethinyl estradiol 1 1 mg norethindrone) at 2 weeks postpartum. 80 This study found that there was no difference in continuation of breastfeeding between the 2 groups at 8 weeks (64.1% combined pills vs 63.5% progestin only) or 6 months. 80 In both groups, women who supplemented their infants with formula or had concerns of inadequate milk supply were more likely to stop breastfeeding.…”
Section: Contraceptivesmentioning
confidence: 79%
“…80 This study found that there was no difference in continuation of breastfeeding between the 2 groups at 8 weeks (64.1% combined pills vs 63.5% progestin only) or 6 months. 80 In both groups, women who supplemented their infants with formula or had concerns of inadequate milk supply were more likely to stop breastfeeding. 80 It should be noted that there was no comparison of discontinuation rates of breastfeeding with a placebo group, so it is unknown whether progesterone itself increased the rates of discontinuation, and only the mother's perception of changes in milk volume, not actual volume measurements, were analyzed.…”
Section: Contraceptivesmentioning
confidence: 79%
See 1 more Smart Citation
“…33 Newer studies show that combined oral contraceptives may be initiated in low-risk, breast-feeding women as early as four weeks postpartum without compromising lactation. 82 However, availability of contraceptive methods immediately following pregnancy may not be sufficient; intensive counseling may be needed to enhance their uptake. 85 …”
Section: Approaches To Reduce Rapid Repeat Pregnancies Among Adolescementioning
confidence: 99%
“…47,77 Similarly, the safety, efficacy, and acceptability of implant placement during the delivery hospitalization and high continuation rates have been well documented, 47,75,[77][78][79][80][81] even in women who plan to breastfeed their infants. 82,83 Recognizing these benefits, Medicaid programs in over a dozen states now provide full coverage for provision of both implants and IUDs as inpatient procedures.…”
Section: Approaches To Reduce Rapid Repeat Pregnancies Among Adolescementioning
confidence: 99%